The Influence Of Murottal Therapy Of Surah Ar-Rahman On Pre-Operative Anxiety Of Patients Undergoing Caesarean Section With Spinal Anesthesia - Deni rahman; Amin Sutanto; Emiliani Elsi Jerau (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Anxiety is a common psychological problem experienced by patients before undergoing surgical procedures, including cesarean section under spinal anesthesia. Uncontrolled anxiety may negatively affect physiological stability and interfere with the success of medical procedures. Recitation of the Holy Qur’an (murottal) is recognized as a non-pharmacological intervention capable of inducing relaxation and reducing anxiety. This study aimed to determine the effect of murottal recitation of Surah Ar-Rahman on anxiety levels among pre-operative cesarean section patients at RSU An Ni’mah Wangon. A pre-experimental one-group pretest–posttest design was used involving 37 respondents selected through purposive sampling based on inclusion criteria. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after a 15-minute Surah Ar-Rahman audio recitation. Data were analyzed using paired statistical tests (Paired Sample T-Test or Wilcoxon Signed-Rank Test), with the Wilcoxon test applied due to non-normal data distribution. The results showed that before the intervention, most respondents experienced moderate (43.2%) and severe (40.5%) anxiety. After the murottal recitation, anxiety levels decreased significantly (p < 0.05). A small number of respondents remained in the severe anxiety category, potentially due to high baseline anxiety, limited intervention duration, and individual factors such as spiritual engagement and family support. In conclusion, murottal recitation of Surah Ar-Rahman effectively reduced anxiety in pre-operative cesarean section patients under spinal anesthesia. The novelty of this study lies in its focus on a specific surgical population and its evaluation of Surah Ar-Rahman as a structured, standardized, and practical non-pharmacological intervention for anesthesiology nursing practice.